Gender at the border: Uneven development in Post-Socialist Hungary - D Momsen, Janet; Iren K Szorenyi, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2007)
Borders can be seen as the clearest spatial products of the geopolitical changes since 1989 in Eastern Europe. In post-socialist countries, inextricably linked to the transition to democracy was the encouragement of private enterprise, which has been seen as having, generally, detrimental effects for both women and rural areas. However, these changes introduced an element of choice into the lives of women and men by increasing the range of possibilities and opportunities for livelihood strategies which differed between urban and rural areas. This paper compares gender and entrepreneurship in east and west Hungary. Principal components analysis was employed to interpret the village level data. Social capital involving linkages outside the village and across the international border was shown to be more important in western Hungary than in the east. The newly acquired freedom to develop a business has enabled previously undervalued entrepreneurial skills to be utilised, and encouraged flexible specialization and contingent labour practices, while bringing greater prosperity and a wider range of services to villages in Hungary